A Study on River Ecotourism Development: Case Study: Karaj River - Goharipour, Hanieh; Hajiluie, Masoud Mahdavi (International Journal of Geography and Geology, 2016)
Tourism industry considered as the largest and most diverse industry in the world. Many countries face this dynamic industry as the main source of income, local community Employment, infrastructure, and private sector development. One of the most popular branches of tourism is ecotourism referring as sustainable tourism, green tourism or responsible tourism, which is the most popular branch of tourism. In terms of geographical location, climate variability, and complexity of natural attractions, Iran is a unique country enjoying great tourism potentials that can create job, currency, and economic growth, particularly in deprived inaccessible areas. However, unfortunately, little attention paid to this tourism category yet. Iran's rivers are one of the most important ecotourism resources and have many capabilities for scientific planning. Given the high potentials of Karaj River such as sufficient width, river depth, and its suitable stream for rafting, local people's familiarity with rafting, access to roads, and other natural, historical and cultural attractions near Karaj River as well as the development of river ecotourism will be discussed in this study. Karaj River and its environment are programmable ecotourism attractions; and many planning projects offered to sustainably utilize this river for the purpose of employment, ecotourism sustainable development, conserving natural environment, cultural promotion, creating positive experiences between the host and guest society, creating fun and excitement among families, sport tourism development and promoting rafting. This research uses ecological McHurg Model, and library and field studies, including multiple river exploration, and rafting, and using GIS software. It is hoped that the present study used to promote tourism goals in the region and even international level.